Acceptability and usability of oral fluid-based HIV self-testing among female sex workers and men who have sex with men in Morocco - Amal Ben Moussa; Ouijdane Belhiba; Fatima Zahra Hajouji; Amina El Kettani; Mohammed Youbi; Kamal Alami; Boutaina El Omari; Lahoucine Ouarsas; Mehdi Karkouri (BMC, 2022)
Abstract Background In 2020, almost 20% of people living with HIV (PLHIV) in Morocco are still unaware of their HIV status. Under these circumstances, HIV self-test (HIVST) can be an efficient additional tool for improving the testing rates in Morocco and reaching the first objective of the UNAIDS 95-95-95 goal. ALCS, a Community-based organization, involved in HIV Testing since 1992, and the Ministry of Health of Morocco conducted, a study on the acceptability and usability of HIVST among Female sex workers (FSW) and MSM (men who have sex with men), using a salivary rapid test. To our knowledge, this is the first study in Morocco exploring these parameters. Methods We conducted a pilot study on the usability of the OraQuick HIV-1/2 salivary self-test among MSM and FSW visiting the ALCS centers for standard HIV rapid testing in five Moroccan cities. Participants chose whether or not to be assisted by lay provider HIV testing. The counselors sampled them to perform a standard rapid test and then invited them to a private room to perform the HIV self-test simultaneously. In addition, a questionnaire was administered to collect socio-demographic data and to assess their opinion about the usability of the salivary HIVST. Results Our study was carried out for 5 months and included 492 participants (257 MSM and 233 FSW). The average age of the participants was 29 years among MSM vs 34 years among FSW. The FSW have a lower educational level, 28,8% of them are Illiterate vs. 6,1% of the MSM. Only 18% of participants were aware of the existence of the HIVST, nevertheless, we recorded a very high rate of acceptability (90,6%) of the HIVST. Performing the HIVST was deemed very easy for 92,2% of MSM versus 80,6% of FSW. Although it was found very difficult for six participants, including five FSW, 4 of them could not read or write. Overall, the study registered a high HIV positivity rate (3,8%) and 100% of concordance between HIVST participants' interpretation and standard HIV testing performed by ALCS lay provider HIV testing. Conclusion Our study shows very high acceptability of HIVST among FSWs and MSM in Morocco, HIV self-testing is still unknown by key populations in Morocco, and the low level of education of FSWs may be a barrier to the use of this test, but with the proposed assistance and adapted demonstration tools, the HIV self-testing will certainly improve access to testing in Morocco.